Aura Budaya dalam Polykria - Junaidi, Alip Supar; Toekio, Soegeng (KEMADHA, 2011)
When the mass emotions appear to be part of the social dynamics are very different  in scale, appear various opinions. There  is a kind of pressure and sudden action, when life disturbed by the policies and the ease with which it is not  considered  correlative.  Problems  and  action  seemed  to  come simultaneously into clumps in the act. Among the many problems that must be faced, whether  they are positive or negative, seems  to never go completely dibincangkan.While men have always regarded as a maker-made; initiators, actors, even users of natural resources  is very greedy; often get attitude pros and cons. Another  phenomenon;  form  reclamasi  action,  such  reforestation  or conservation plan burst like the scale of urgency. This side was the tendency of trace some aspects that characterized the presence of a work of art that cares for  the  environment.  A  moment  comes  which  depart  from  the  vigorous performance of environmental  information and  scroll  to  the art.One might define good and evil, right and wrong or something more leads  to ambivalent. Ambiguous condition was apparently also  implied  the treasures  of  art,  where  the  conventional  structure  is  confronted  with  a moderate  reform. Artistic  treasures are  faced with  two options open areas. Thats all fine. However the choice should remain grounded in the wisdom that leads  to  the  front and opened  the optimism  in entering  the global competition.